Efektivitas Penggunaan Media Vibermixo Dalam Meningkatkan Motivasi Belajar Siswa Pada Mata Kuliah Akuntansi: Berdasarkan Tinjauan Literatur - Mattoasi Mattoasi (Jambura Economic Education Journal, 2019)
Learning is a complex and unique process, meaningthat someone who learns involves all aspects of hispersonality, both physically and mentally. The involvementof all aspects of personality is expected tohave an impact on students with the support of adequatelearning media. The purpose of this study is tofind out the appropriate learning media in the accountingsphere based on the literature. The research methodused is a qualitative method by using library researchas a data source. The results showed that the use ofVibermixo media in the accounting learning processcould be used to improve the quality with student.